2017
DOI: 10.4038/slja.v25i2.8200
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of King Vision video laryngoscope (channelled blade), McCoy, and Macintosh laryngoscopes for tracheal intubation in patients with immobilized cervical spine

Abstract: Background: Cervical spine immobilization results in a poor laryngeal view on direct laryngoscopy leading to difficulty in intubation. This randomized prospective study was designed to compare the laryngeal view and ease of intubation with the Macintosh, McCoy, and King Vision video laryngoscopes in patients with immobilized cervical spine. Method: Ninety adult patients of ASA grade I-II with immobilized cervical spine using manual inline axial cervical spine stabilization technique, undergoing elective cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
2
16
0
2
Order By: Relevance
“…Prior studies done by Ali et al . [ 1 ] and Bharti et al .,[ 3 ] respectively, have shown that KV and TV significantly improve laryngoscopic view as compared to Macintosh and McCoy in cervical spine immobilization. We additionally found that KV gives better IDS versus TV EVO2 ( P = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies done by Ali et al . [ 1 ] and Bharti et al .,[ 3 ] respectively, have shown that KV and TV significantly improve laryngoscopic view as compared to Macintosh and McCoy in cervical spine immobilization. We additionally found that KV gives better IDS versus TV EVO2 ( P = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al noticed that increase in HR and mean arterial pressure (MAP) was less with KVVL as compared with the Macintosh laryngoscope. [15] Elhadi et al also found a significant rise in HR and MAP in the Macintosh group compared with the KVVL group. [16] We did not see any significant difference in hemodynamic parameters between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…First attempt success rate at intubation was significantly greater in this study, 92 vs 74%, which is in agreement with the study by Ali et al ; however, Elhadi et al did not find any significant difference. [1516]…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ali et al . [2] has shown an improvement in the Cormack–Lehane grade using the King Vision laryngoscope compared with the Macintosh laryngoscope. Our study also is in keeping with the observations made by Ali et al .…”
Section: Discussionmentioning
confidence: 99%
“…The nonchanneled blade, which we used in this study, requires a minimum of 13-mm mouth opening and thus may be potentially useful in patients with limited mouth opening. [2]…”
Section: Introductionmentioning
confidence: 99%